2020
DOI: 10.1017/s0022029920000515
|View full text |Cite
|
Sign up to set email alerts
|

Effects of suckling on milk yield and milk composition of dairy cows in cow–calf contact systems

Abstract: In this research communication I show the effect of various cow–calf contact systems on milk yield and milk composition during the periods when calves where allowed to suckle their dams and after the calves were separated in comparison to cows that were only machine milked throughout their lactation. Analyses were based on four different experiments, but conducted at the same research station and under comparable housing and feeding conditions. Nursing dams had contact to their calves during the whole day, dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 17 publications
3
30
0
Order By: Relevance
“…In the separation phase, the machine milk yield increased to 25.0 ± 10.37 kg/d, with only subtle differences between the groups. After separation, machine milk yields of CCC cows were comparable to those recorded for non-nursing cows (Meagher et al ., 2019), although no direct comparison was made and is quite possible that the suckling system may affect post-separation yields (Barth, 2020). The increased AMS milk yield is also in line with the estimated amount of milk drunk by suckling calves (Johnsen et al ., 2015).…”
Section: Resultsmentioning
confidence: 99%
“…In the separation phase, the machine milk yield increased to 25.0 ± 10.37 kg/d, with only subtle differences between the groups. After separation, machine milk yields of CCC cows were comparable to those recorded for non-nursing cows (Meagher et al ., 2019), although no direct comparison was made and is quite possible that the suckling system may affect post-separation yields (Barth, 2020). The increased AMS milk yield is also in line with the estimated amount of milk drunk by suckling calves (Johnsen et al ., 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, the overall incidence of mastitis was comparatively high in both groups and probably due to deficiencies in husbandry and milking hygiene. Other authors either detected no influence of suckling on the SCC [4] or a slight increase [41]. The latter may be a consequence of the combination of both milking and suckling, which places more stress on the teats.…”
Section: Bacteriological and Cytological Cure Ratementioning
confidence: 91%
“…However, farmers have concerns with the amount of milk returned to the milking parlor by the cows (Ventura et al, 2013). Studies have shown higher variation in milk yield among cows that are suckled by calves in a cow-calf contact system compared with those in a conventional milking parlor system (Bar-Peled et al, 1995;Barth, 2020). A Scottish farmer practicing the cow-calf contact system has also observed a wide variation in milk yield to the parlor by cows in his farm, with some cows giving as little as 1 L/d and some as much as 15 L/d (D. Finlay, Rainton Farm, Dumfries and Galloway, Scotland; personal communication).…”
Section: Jdsmentioning
confidence: 99%